STRATEGI PENINGKATAN PENDAPATAN ASLI DAERAH (PAD) SEKTOR KELAUTAN DAN PERIKANAN KABUPATEN TOLITOLI - Novrianti, Ade Anita (Katalogis, 2015)
This type of research is descriptive analytic with the number of respondents consisted of 89 people, spread across two regions, such as, District Galang and Baolan. SWOT analysis and contribution analysis are used as analytical method. The results show that (1) there was 0,004063% contribution derived from marine and fisheries sector to locally generated revenue in 2014 which equal to USD 188.496.400 out of the target Rp 200.000.000 (2) SWOT analysis indicates that the internal condition consists of strengths and weaknesses. The capabilities factors include the strength of fishery processing, higher production of fisheries are supported by the potential for marine. In addition, Regional Regulation No. 4. 2012 on business license levy in fisheries and local regulations No. 7. 2012 on auction levy. On the other hand, the weakness factors include inadequate fishing equipments, conflict fishermen, fishing communities of limited resources, the fishery and collector levy and guidance to the fishing communities remains low. Meanwhile, the external conditions consist of opportunities and threats. Factors opportunities include local taxes and levies, the area of ​​the arrest, the potential of marine and fisheries that will not run out and support the government in improving the fishery sector and increase the locally generated revenue. Furthermore, while the threat factors include the threat of climate change to the catch, the occurrence of damage marine ecosystems and fisheries, marine potential retrieval of outsiders and marketing system are less supportive. The formulation strategy of increasing locally generated revenue of marine and fisheries sector Tolitoli located in quadrant I of the expansion strategy. This means that optimizing the power to take advantage by identifying several opportunities is important. This strategy aims to increase fish production by government assistance in accelerating marine and fisheries sector and optimising the local regulation No. 4, 2012 on fisheries business licence levies in order to increase the number of fish production by utilizing the fishing area.